Reflection on the first five years of South Africa's Acoustic Tracking Array Platform (ATAP): status, challenges and opportunities. Issue 4 (2nd October 2017) - Cowley, PD; Bennett, RH; Childs, A-R; Murray, TS
Abstract : The Acoustic Tracking Array Platform (ATAP) is a marine science programme that monitors the movements and migrations of inshore marine animals along the South African coastline. Acoustically tagged animals are monitored by an expanded network of approximately 100 automated data-logging acoustic receivers moored at strategic node sites, from Cape Point in the west to the South Africa–Mozambique border in the east. During five years since its inception, in 2011, the ATAP has achieved outstanding progress in terms of the numbers of animals and the variety of species tagged. To date, the ATAP has yielded over 2.6 million detections from more than 700 acoustically tagged animals, representing 27 different species from 20 families, including the African penguin Spheniscus demersus, fishery-at-risk species (e.g. dusky kob Argyrosomus japonicus ) and iconic elasmobranchs (e.g. white shark Carcharodon carcharias ). Following a period of considerable equipment loss in 2014, refinement of the receiver network was required and the deeper receivers at each site were decommissioned without influencing the integrity of the nationwide array. The platform, managed by the South African Institute for Aquatic Biodiversity, ultimately represents a low-cost method of collecting long-term data that currently benefits approximately 25 researchers from 14 organisations. Case studies are presented to expose the opportunities provided by the ATAP, which will undoubtedly yield new discoveries and provide a greater understanding of the movement patterns and migrations of a wide variety of inshore marine and estuary-associated species.